An Analysis of Students’ Reading Interest in New Normal Era - Thariy Wulansari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2023)
This research aims to analyze the students reading interest in new normal era, in academic year 2019/2020. This research is a descriptive research. The writer chose the sample by using random sampling technique.It involved one class from grade IX Ahmad Yani Junior High School 1 Bangkinang Kota that consisted of 32 students. The writer distributed questionnaires to 32 students and took 5 students to be interviewed. To answer the research question, the questionnaires were distributed and the writer do interview for 5 students. It doto know the students’ reading interest in new normal era and the differences of book media in new normal era. After collecting the data, the result of this research showed that students had high interest in reading during the pandemic. It was also supported by the result of the questionnaire. The percentage was 62.5%. The students mostly interested to read because that their hobby and they do reading activity during the pandemic. While in book media during the pandemic, the student feel difference with book media in face to face. The result, the students more easy, simpler and save their time to reading a book without bring the book enywhere or anytime. Based on the results of the research, the writer concluded that the students had high reading interest although in pandemic situation and they take the advantages from the technology in New Normal Era.